Effectiveness of carbon dioxide in compressed gas or solid formulation for the control of insects and mites in stored wheat and barley - White, N.D.G.; Jayas, D.S. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
Carbon dioxide can be used as an effective stored-grain fumigant in relatively air-tight bins. Carbon dioxide was added to wheat (Triticum aestivum) as a compressed gas and to barley (Hordeum vulgare) as a solid (dry ice) in 322-kg grain bulks. Wheat was stored at temperature decreasing from 18 to 10°C over a 12-wk period. Bins were left open, sealed without C02 added, or with C02 supplemented at 25,34, and 46% levels. Barley was stored at temperature decreasing from 25 to 20°C over an 8-wk period. Bins were left open, sealed without C02 added, or with C02 treatments of 23, 29, and 34%. The wheat and barley moisture content were 14.5-16.3% and 14.5-16.1%, respectively. Oxygen levels in the wheat reflected air displacement with C02, but lower O2 levels in the barley reflected a combination of air displacement by C02 and consumption of O2 by respiring grain and microorganisms at the warmer temperatures. The insects Cryptolestes ferrugineus and Tribolium castaneum were controlled in 2 wk at 34% C02 and 15% O2 at temperature decreasing from 18 to 10°C, or 29% C02 and 3% O2 at temperature decreasing from 25 to 20°C. The mites Tarsonemus granarius, Lepidoglyphus destructor, and Aeroglyphus robustus were killed in less than 2 wk at these C02 levels. Seed germination and microflora were unaffected by all gaseous environments.